System for analytical monitoring of vibrational behavior in a gas compressor - Segura Benavides, Hugo; Porras Niño, Carlos Andres; Montaña Quintero, Henry (Visión electrónica, 2014)
The purpose of this article is to monitor the vibrational behavior of the gas compressor Worthington, with a global view point system process production plant Turgas S.A. ESP, about a PC in the control room, for reasons of comfort and safety. Thus this technology with safe and timely decisions, real time, taking into account the relative dangers of natural gas. By monitoring the vibration level compressor wanted quality improvement process, production weather facilitates work and reduces costs. Additionally, the research project aims to develop a technique that allows the noun, plural follow vibrational analysis applied to predictive maintenance, for machine stoppages and thus evaluate when are necessary preventive maintenance scheduled so avoiding unwanted accidents operational personnel, disruption the environment, apart from expensive damage in electrical or mechanical components represented in volume production, time and money invested for Company.